Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3389/fphar.2010.00147
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Laboratory Pre-Validation of a Human Cell Based in vitro Angiogenesis Assay for Testing Angiogenesis Modulators

Abstract: The developed standardized human cell based in vitro angiogenesis assay was intra-laboratory pre-validated to verify that the method is reliable and relevant for routine testing of modulators of angiogenesis, e.g., pharmaceuticals and industrial chemicals. This assay is based on the earlier published method but it was improved and shown to be more sensitive and rapid than the previous assay. The performance of the assay was assessed by using six reference chemicals, which are widely used pharmaceuticals that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 70 publications
5
43
1
Order By: Relevance
“…This might complicate the use of commercial media in toxicological studies as medium components may interact with test compounds. In addition to commonly used VEGF and FGF-2 defined by us earlier (Sarkanen et al, 2011), we found that the network formation can be further improved by addition of AA, HE and HY. Ascorbic acid (vitamin C) is an essential nutrient for human endothelial cells necessary for their effective migration and for the synthesis of collagen type IV, an important component of basement membrane (Telang et al, 2007).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This might complicate the use of commercial media in toxicological studies as medium components may interact with test compounds. In addition to commonly used VEGF and FGF-2 defined by us earlier (Sarkanen et al, 2011), we found that the network formation can be further improved by addition of AA, HE and HY. Ascorbic acid (vitamin C) is an essential nutrient for human endothelial cells necessary for their effective migration and for the synthesis of collagen type IV, an important component of basement membrane (Telang et al, 2007).…”
Section: Discussionmentioning
confidence: 54%
“…Isolation and culture of human umbilical vein endothelial cells HUVEC were isolated from human umbilical cord veins using 0.05% collagenase I as described previously (Sarkanen et al, 2011). The cells were cultured in EGM™-2 Endothelial Cell Growth Medium-2 (EGM-2, Lonza Group Ltd).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this prevascular-like network model, cells are induced with natural growth factors and allowed to self-assemble into tubular network and vascular supporting structures. We studied the hASC+HUVEC coculture model by combining some properties and analyses from previous studies [Friis et al, 2003;MerfeldClauss et al, 2010] and the fibroblast-HUVEC coculture angiogenesis assay previously validated in our laboratory [Sarkanen et al, 2011]. We induced the hASC+HUVEC coculture or hASC monoculture with naturally occurring angiogenic growth factors; epidermal growth factor, VEGF, bFGF and IGF-I [Mehta and Besner, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that a linear dose-response relationship exists between the VEGF-A concentration and the tube formation potency in the co-culture assay in which concentrations of 10 ng/mL VEGF-A and 1 ng/mL FGF-2 are required for maximum response [29]. Our data demonstrated that the tube formation capacity of ASC-CM, even at passage 6, was equivalent or higher than that of medium containing 10 ng/mL VEGF-A as positive control (see Figure 4).…”
Section: Discussionmentioning
confidence: 99%